On the Democratisation of Science Education through Facebook: Implications for Autonomy, Equality and Teacher Education in Universities - Waghid, Faiq (South African Journal of Higher Education, 2016)
In this article I offer a defence for using educational technology to democratise classroom practices in relation to science education and teacher education at universities. My contention is that educational technology, more specifically using Facebook, can engender pedagogical action amongst learners and educators that resonates with democratic practices. In other words, using educational technology in science and teacher education can enhance learner autonomy and equality, so that critical, self-reflexive thinking and disruptive thought and action respectively can be cultivated through technology-assisted education. Keywords: Education, democracy, autonomy, equality and technology